Makna di Balik Tradisi Mitoni dalam Budaya Jawa: Teori Ikonologi-Ikonografi - Putra, Muhammad Alfero Kumara (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2025)
This article was created to add insight into the Mitoni tradition to the readers. This research aims to find out and describe every meaning contained in the Mitoni Tradition procession. In this research, using qualitative research methods. Sources of data taken using data derived from journals, books and interviews. Mitoni tradition is a ritual performed for pregnant women who have entered the age of seven months, derived from the words 'am' and 'pitu'. This tradition has several stages, namely, sungkeman, siraman, ganti busana, brojolan, and slametan. The timing of the Mitoni tradition cannot be arbitrary and must be in accordance with the calendar before the full moon. Each procession has its own meaning. Although they have different meanings, the point is the same, namely, the hope of prospective parents so that the baby who is conceived is given health and given smoothness during the delivery process.